Secure remote sensor simulator for heavy vehicle electronic control units - Gannavarapu, Ram Rohit, author; Chong, Edwin, advisor; Pasricha, Sudeep, committee member; Daily, Jeremy, committee member (Colorado State University. Libraries, 2022)
Heavy Vehicle Event Data Recorders (HVEDRs) have the capability to record crash-related data and are valuable tools for traffic crash investigators. The data extracted from HVEDRs contain information to help reconstruct the driver's behaviors and determine the events leading to a crash. Data extraction is commonly performed using diagnostic tools when the electronic control unit (ECU) with the HVEDR is available on the vehicle's network. In the cases where the electrical system of the vehicle is compromised, the ECU is often removed and connected to a harness for power and communications. These harnesses are not designed to preserve fault codes or diagnostic trouble codes which can result in overwriting data related to a particular crash event. This thesis describes the open-source hardware and software design of a remotely accessible sensor simulator used to create a fault-free environment for a bench download of an HVEDR. The sensor simulator device reduces the chance of any alteration of the original fault code data inside the HVEDRs by emulating the presence of actuators and sensors to the ECU. It does this using analog voltage outputs, pulse-width modulated signals, digital potentiometers, and CAN messages. The settings for these are adjustable remotely through a web-based interface. A contribution of the thesis focuses on a process to increase the security posture of the embedded IoT devices wherein it utilizes a hardware security module to offload cryptography operations. The hardware security module was also used for secure key storage and implement Elliptic Curve Digital Signature Algorithm (ECDSA) to sign and verify messages for integrity, which is a key process in Transport layer security (TLS). The device also securely connects to a cloud infrastructure using TLS, enabling investigators to operate these devices remotely using a web-based graphical user interface. Secure remote access enables further research and investigation of heavy vehicle electronic systems.